Edukacja XXI wieku : strategie zarządzania i kierunki rozwoju - Krawczyńska-Zaucha, Tatiana (2020)
EDUCATION OF THE 21ST CENTURY MANAGEMENT CHALLENGES AND DEVELOPMENT TRENDS Education of the 21st century is divided into four parts. Part one encourages you to look at education from a broader, global perspective. It invites to focus on: changing the way of thinking about education and methods for passing on knowledge, showing different patterns and strategies of management and educational leadership, and bringing the conditions of education closer to a multicultural context. Part two addresses the ethical aspects of education by proposing a specific objective for teaching ethics in schools, raising the issue of human/animal attitudes, and showing the approaches developed against educational failure. Part three discusses in more detail innovative educational approaches, starting from a review of educational options currently available in Poland, through building relationships with students and methods which encourage them to take up creative challenges, to choosing strategies for modern teaching in selected contexts. Finally, part four deals with selected methods and tools that can be used in the twenty-first century education.
Keywords: education of the 21st century; educational trends; educational management; leadership in education (educational leadership); innovative educational tools